Математичні компетенції студентів природничих спеціальностей - Месарош Лівіа; Livia Mesarosh; Mészáros Lívia (Видавничий дім «Гельветика», 2023)
Abstract. Training based on a competency-based approach involves not just mastering one or another discipline by students, but the ability to use the acquired knowledge in their future professional activities. The material of this article is devoted to such an important issue as the mathematical competencies of students of natural sciences, since these competencies contribute to the adequate application of mathematics for solving problems of everyday life. The purpose of the article is to substantiate the importance of acquiring mathematical competences for the successful further professional activity of students of natural sciences. In addition, it is aimed promoting a better study of the disciplines of the natural and mathematical cycle in higher educational institutions, highlighting their importance and applied nature. The paper shows that a necessary characteristic of a highly qualified specialist is mathematical competence. In the process of mathematical training, students of natural scienc es should be involved in educational activities that would contribute to the formation of critical thinking in them, the ability to apply mathematical methods of research, and the use of already acquired mathematical knowledge in other fields of science, knowledge of information and communication technologies, the ability to apply methods mathematical (informational) mode ling, the ability to apply abstract thinking processes, in new fields of research and to achieve new scientific results.It has been established that a high level of mathematical competence significantly increases competitiveness in the labor market, contrib utes to the successful career growth of students, future specialists in natural sciences. It is shown that mathematical training should be aimed at the formation of mathematical competence in students, because the level of formation of the professional competence of a future specialist in natural sciences largely depends on its quality.

Резюме. Навчання, що базуються на компетентнісному підході передбачає не просто освоєння студентами тієї чи іншої дисципліни, а вміння використовувати набуті знання у своїй майбутній професійній діяльності. Матеріал даної стат ті присвячений такому важливому питанню, як математичні компетенції студентів природничих спеціальностей, оскільки саме вони сприяють адекватному застосуванню математики у повсякденному житті та майбутній кар`єрі. Метою статті є обґрунтувати важливість набуття математичних компетенцій для успішної подальшої професій ної діяльності студентів природничих спеціальностей, сприяти кращому вивченню дисциплін природничо-матема тичного циклу у вищих навчальних закладах, вказавши на їх важливість та прикладний характер. У роботі показано, що необхідною характеристикою висококваліфікованого фахівця є математичні компетенції. У процесі математич ної підготовки студенти природничих спеціальностей мають бути залучені до навчальної діяльності, яка б сприяла формуванню в них критичного мислення, здатності до застосування математичних методів досліджень, та викори стання вже набутих математичних знаннь в інших галузях науки, знання інформаційно-комунікаційних технологій, вміння застосувти методи математичного моделювання, здатності застосовувати абстрактні процеси мислення, у нових галузях досліджень та для досягнення нових наукових результатів. Встановлено, що високий рівень матема тичної компетентності значно підвищує конкурентоспроможність на ринку праці, сприяє успішному кар’єрному рос ту студентів, майбутніх фахівців природничих спеціальностей. Показано, що математичну підготовку слід націлити на формування математичної компетенції у студентів, адже від її якості в значній мірі залежить рівень сформованості професійної компетентності майбутнього фахівця природничих спеціальностей.
Mathematical competencies of science students
Keywords: математична компетентність; математична підготовка; mathematical competence; mathematical preparation